Por trás das compras sustentáveis do Governo Federal: uma análise dos atores envolvidos no processo de transformação das aquisições federais - Louzada, Guilherme Neves Piedade (2016)
The great economic development in the post World War II period brought great pressure on the environment and natural resources forcing the theoretical currents of the economy to consider this issue in their analysis. In the development of the analysis of the relationship between economy and environment, the consumer gets a prominent role as a major contributor to the pressure on the environment. The advent of the Green Economy concept puts the state in the protagonist condition for the transition to a low carbon economy. In this research haul the first looks on sustainable procurement federal program, seen as one of the programs responsible for the transition to a green economy. Through the analysis of academic and professional trajectories of the actors who are behind the development of sustainable public procurement in Brazil, I point out that there is a vanguard of political actors in the Northeast in the development of legislation that encourages sustainable procurement and the existence of a strongly established elite in partnership between ICLEI, EAESP / FGV and British Embassy.